Non-zero sum games on the unite square with the different curves of discontinuity of the kernels - Sūdžiūtė, D. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Д. Суджюте. Неантагонистические игры на единичном квадрате с различными кривыми разрыва ядер игры D. Sūdžiūtė. Neantagonistiniai lošimai vienetiniame kvadrate su skirtingomis branduolių trūkio funkcijomis